Characterization of konjac glucomannan-based active films loaded with thyme essential oil: Effects of loading approaches. (March 2022) - Liu, Zhe; Lin, Dehui; Li, Nan; Yang, Xingbin
Abstract: The aim of this study was to compare the characterization of konjac glucomannan (KGM)-based active films loaded with thyme essential oil (TEO) via different approaches. KGM-based active films were loaded with TEO via four approaches (Approach Ⅰ: TEO only, approach Ⅱ: TEO and Tween 80, approach Ⅲ: TEO and bacterial cellulose nanofibers/soy protein isolate (BCNs/SPI) composite colloidal particles, approach Ⅳ: TEO-loaded Pickering emulsions stabilized by BCNs/SPI composite colloidal particles), and the characterization of the corresponding four types (type Ⅰ, Ⅱ, Ⅲ, and Ⅳ) of active films were investigated. The results showed that the microstructures of type II and type IV films were smoother and more compact than those of type Ⅰ and Ⅲ films. Furthermore, the hydrophobicity of type Ⅲ and type Ⅳ films was higher as compared with that of type Ⅰ and type Ⅱ films. Moreover, the physical properties of KGM-based active films loading TEO via approaches Ⅱ, Ⅲ, and Ⅳ were improved. Especially, type Ⅳ film presented the most excellent properties among the four types of active films. Additionally, type Ⅳ film displayed the highest total phenol content and antioxidant capacities, as well as the best TEO-release property. Therefore, this study suggested that the TEO-loading approach via Pickering emulsions was the most effective way to improve the properties of the KGM-based active films. Graphical abstract: Image 1 Highlights: KGM-based active films loaded with TEO via four approaches were compared. TEO-loading via Pickering emulsions was the best approach to improve film properties. The TEO-loaded KGM films have a great potential application in food packaging.